Acute Liver Failure from Tumor Necrosis Factor-α Antagonists: Report of Four Cases and Literature Review - Kok, Beverley; Lester, Erica L. W.; Lee, William M.; Hanje, A. James; Stravitz, R. Todd; Girgis, Safwat; Patel, Vaishali; Peck, Joshua R.; Esber, Christopher; Karvellas, Constantine J. (Digestive diseases and sciences, 2018)
Background Tumor necrosis factor-α antagonists (anti-TNF-α) have been associated with drug-induced liver injury. However, cases of anti-TNF-α-associated acute liver failure have only been rarely reported. Aims To identify cases of anti-TNF-α-associated acute liver failure and evaluate patterns of liver injury and common characteristics to the cases. Methods The United States Acute Liver Failure Study Group database was searched from 1998 to 2014. Four subjects were identified. A PubMed search for articles that reported anti-TNF-α-associated acute liver failure identified five additional cases. Results The majority of individuals affected were female (eight of nine cases). Age of individual ranged from 20 to 53 years. The most common anti-TNF-α agent associated with acute liver failure was infliximab ( n = 8). The latency between initial drug exposure and acute liver failure ranged from 3 days to over a year. Of the nine cases, six required emergency LT. Liver biopsy was obtained in seven cases with a preponderance toward cholestatic–hepatitic features; none showed clear autoimmune features. Conclusions Anti-TNF-α-associated acute liver failure displays somewhat different characteristics compared with anti-TNF-α-induced drug-induced liver injury. Infliximab was implicated in the majority of cases. Cholestatic–hepatitic features were frequently found on pre-transplant and explant histology.